The Real Old-Time Religion: Towards an Aesthetics of Neo-Pagan Song - Magliocco, Sabina; Tannen, Holly (Ethnologies, 1998)
This paper, based on dialogic fieldwork and close collaboration between the ethnographer and the tradition-bearers, examines Wiccan and Neo-Pagan musical performance practice. In the absence of a single unifying text or body of beliefs, songs may actually serve to codify and diffuse a shared set of principles in Wiccan and Neo-Pagan folk culture. The paper delineates various categories of songs, examines their role in Wiccan and Neo-Pagan ritual, and explores how emic critiques of music illuminate areas of conflict and tension within the movement. It attempts to delineate an emerging aesthetic of Neo-Pagan song, one that is syncretic, participatory, anti-authoritarian, Romantic and woman-centered, reflecting the movement’s counter-cultural values.